2021
DOI: 10.3390/ijerph182413079
|View full text |Cite
|
Sign up to set email alerts
|

Family Caregivers of People with Dementia Have Poor Sleep Quality: A Nationwide Population-Based Study

Abstract: Previous studies have documented cognitive impairments, psychological stress, and depressive symptoms in family caregivers of people with dementia (PWD), which could be attributed to their sleep disturbances. Notwithstanding the increasing recognition of poor sleep quality and sleep disturbances in family caregivers of PWD, their association has not been tested yet using population-representative samples. We conducted a retrospective, cross-sectional study using population-based data from the 2018 Korean Commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…The deleterious impacts of family caregiving on mental and physical as well as cognitive functions have also been demonstrated in prior investigations. More specifically, the family caregivers of patients with various dementia disorders were more likely to have an increased risk of cardiovascular diseases [ 74 , 75 , 76 ], poor physical health status [ 13 , 16 , 24 ], poor psychological health status including strain, depression, and anxiety [ 25 , 77 , 78 , 79 ], sleep disturbances and poor sleep quality [ 19 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], and cognitive impairments [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Consistent with the aforementioned studies, the fully adjusted model of the current study disclosed that caregivers had a higher frequency of diabetes mellitus, hypertension, depression, subjective cognitive decline, and poor sleep quality relative to noncaregivers (all p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The deleterious impacts of family caregiving on mental and physical as well as cognitive functions have also been demonstrated in prior investigations. More specifically, the family caregivers of patients with various dementia disorders were more likely to have an increased risk of cardiovascular diseases [ 74 , 75 , 76 ], poor physical health status [ 13 , 16 , 24 ], poor psychological health status including strain, depression, and anxiety [ 25 , 77 , 78 , 79 ], sleep disturbances and poor sleep quality [ 19 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], and cognitive impairments [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Consistent with the aforementioned studies, the fully adjusted model of the current study disclosed that caregivers had a higher frequency of diabetes mellitus, hypertension, depression, subjective cognitive decline, and poor sleep quality relative to noncaregivers (all p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…The sample size is 900 participants in each of the 254 community health units located in 17 metropolitan cities and provinces, and the expected total number of participants is 228,600. The KCHS utilized a two-stage sampling procedure to assure a better representation of the general population, as described in detail elsewhere [ 33 , 53 ]. A total of 32,612 out of 228,340 participants were ruled out because they did not fill in the survey variables listed in Table 1 and Table 2 , and consequently, 195,728 participants were eventually included in the statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Concretely, our study showed differences between subjective and objective sleep assessments, since WASO was positively associated with cortisol plasma levels, and SE was negatively related to cortisol plasma levels in women. Previous studies have revealed weak or inconsistent correlations of subjective (i.e., PSQI scores) with objective (e.g., actigraphy and polysomnography) measures [ 58 , 59 , 60 ]. In fact, it has been shown that the PSQI and the accelerometer may assess different attributes of sleep [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The level of impairment in PwD is associated with negative outcomes among carers, for example, higher levels of sleep disturbance, stress related conditions, and poorer health [3,[7][8][9][10][11]. Other individual and contextual factors are also associated with poorer health outcomes in carers of PwD, including greater age of the carer, co-habitation with the care-recipient, and a longer duration of being a carer [10,[12][13][14][15], all factors that characterise a spouse carer more so than a non-spouse carer.…”
Section: Factors Associated With Outcomes Of Carementioning
confidence: 99%